Understanding death an introduction to ideas of self and the afterlife in world religions - Sumegi, Angela 1948- (Chichester, West Sussex, United Kingdom Wiley Blackwell, 2014)
This illuminating book examines how different religions understand death, dying, and the afterlife, drawing on examples from Christianity, Judaism, Hinduism, Buddhism, and Shamanism.
1. Understanding death -- 2. Primal perspective on death -- 3. Death in the ancient world -- 4. Jewish perspectives on death -- 5. Christian perspectives on death -- 6. Muslim perspectives on death -- 7. Hindu perspectives on death -- 8. Buddhist perspectives on death -- 9. Daoist perspectives on death -- Index.
Includes bibliographical references and index.
Keywords: Death -- Religious aspects -- Comparative studies; Future life -- Comparative studies